Two Novel Bimetallic Cyano-Bridged Coordination Polymers Containing the 2,2?-(Ethylenedioxy)bis (Ethylamine): Syntheses, Structural, Thermal and Magnetic Properties - Senocak, Aysegul; Karadag, Ahmet; Yerli, Yusuf; Andac, Omer; Sahin, Ertan (Springer, 2010)
Two new cyano bridged bimetallic polymeric complexes, [Ni(edbea)Ni(CN)(4)]center dot 1/2H(2)O (1) and [Cu(mu-edbea)(mu-CN)(2) Ni(CN)(2)]center dot H2O (2) [edbea = 2,2'-(ethylenedioxy)bis(ethylamine)] have been synthesized by adding metal chloride (M = Ni-II and Cu-II), and edbea into [Ni(CN)(4)](2-) in water-ethanol solution and then characterized by elemental analysis, infrared (IR) and electron paramagnetic resonance (EPR) (for only complex 2) spectra, variable temperature magnetic measurement, and thermal gravimetric analysis. The X-ray diffraction crystal structure of complex 2 shows a 2D polymeric chain -edbea(N5,O1)-Cu1-N1C1-Ni(CN)2-C4N6-Cu1-(N6,O2) edbea- in which the Cu-II centers are linked by two cyano and one edbea. The powder EPR spectrum of the complex 2 has shown that Cu-II ions are located in rhombically distorted octahedral sites. The magnetic properties of the coordination polymers have been studied in temperature range of 15-300 K. The magnetic behaviors investigation of complexes 1 and 2 indicated the presence of a very weak antiferromagnetic interaction.
Keywords: Tetracyanonickellate; Cyano-bridged polymeric complexes; 2,2 '-(Ethylenedioxy)bis(ethylamine); Magnetic properties; Thermal analysis